2014
DOI: 10.1002/jbm.a.35219
|View full text |Cite
|
Sign up to set email alerts
|

Effective release of a broad spectrum antibiotic from elastin‐like polypeptide‐collagen composite

Abstract: Preparation of hydrogels that possess an effective antibiotic release profile and better mechanical properties compared to the traditionally used collagen hydrogels has the potential to minimize post-surgical infections and support wound healing. Towards this goal, we prepared elastin-like polypeptide (ELP)-collagen composite hydrogels that displayed a significantly higher elastic modulus compared to the collagen hydrogels. We then characterized the release behavior of the collagen and ELP-collagen hydrogels l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 53 publications
(107 reference statements)
3
25
0
Order By: Relevance
“…A simple method of fabrication involves the addition of ELPs to a material that naturally undergoes gelation . ELPs mixed with collagen solutions form hydrogels when incubated at 37 °C with no additional need for cross‐linkers, due to both direct interactions and water‐mediated hydrogen bonding between the two components . ELPs combined with fibrinogen and thrombin form sponges after covalent bonding between ELPs and fibrin monomers generated from thrombin cleavage of fibrinogen …”
Section: Composite Elp‐based Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…A simple method of fabrication involves the addition of ELPs to a material that naturally undergoes gelation . ELPs mixed with collagen solutions form hydrogels when incubated at 37 °C with no additional need for cross‐linkers, due to both direct interactions and water‐mediated hydrogen bonding between the two components . ELPs combined with fibrinogen and thrombin form sponges after covalent bonding between ELPs and fibrin monomers generated from thrombin cleavage of fibrinogen …”
Section: Composite Elp‐based Materialsmentioning
confidence: 99%
“…Similarly, hydrophobic interactions between ELP and carbon nanosphere chains enhance the strength of such composite hydrogels . ELP‐collagen hydrogels also have a higher tensile strength arising from stronger intermolecular bonding, and a lower elastic modulus . Hybrid ELP‐PEG hydrogels likewise display lower shear storage and elastic moduli .…”
Section: Composite Elp‐based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that antibioticloaded collagen scaffolds, 47 composite fibers comprised of polyglyconate and porous poly(DLlactic-co-glycolic acid) (PDLGA), 48,49 and electrospun nanofibers consisting of biodegradable poly vinyl alcohol and sodium alginate, 50 can reduce infection either in vitro or in vivo. Recently, Albaugh et al combined topical antibiotics with cellulose dressing to fight infection of lower extremity chronic ulcers infected with MRSA.…”
Section: Discussionmentioning
confidence: 99%